Handgrip weakness, low fat‐free mass, and overall survival in non‐small cell lung cancer treated with curative‐intent radiotherapy. Issue 2 (11th February 2020) - Burtin, Chris; Bezuidenhout, Jacques; Sanders, Karin J.C.; Dingemans, Anne‐Marie C.; Schols, Annemie M.W.J.; Peeters, Stephanie T.H.; Spruit, Martijn A.; De Ruysscher, Dirk K.M.
Abstract: Background: Assessment of handgrip strength and fat‐free mass provides quick and objective information on muscle performance and mass that might complement subjective World Health Organization Performance Status (WHO PS). We investigated to what extent the presence of pre‐treatment handgrip weakness and low fat‐free mass index (FFMI) provides additional prognostic information on top of well‐established prognostic factors (including WHO PS) in non‐small cell lung cancer (NSCLC) patients selected for curative‐intent (chemo)radiation. Methods: Prospectively, patients with early and locally advanced NSCLC (stages I‐III) treated with (chemo)radiation were enrolled. Handgrip weakness and low FFMI, derived from bioelectrical impedance analysis, were defined using normative values and were correlated with overall survival (OS). Results: We included 936 patients (age 68 ± 10 years; 64% male; 19% stage I, 9% stage II, and 72% stage III disease; 26% handgrip weakness; 27% low FFMI). In patients with good performance status (WHO PS 0 or 1), handgrip weakness and low FFMI were significant prognostic factors for OS, after adjustment for age, gender, disease stage, and co‐morbidities. The combined presence of handgrip weakness and low FFMI was a strong prognostic factor for OS when compared with patients with normal handgrip strength and FFMI (hazard ratio: 1.79, 95% confidence interval: 1.34–2.40, P < 0.0001). In patients with impaired performance status (WHO PS ≥ 2, 19% of sample), handgrip weakness and low FFMI were not related to OS. Conclusions: In early and locally advanced NSCLC patients treated with curative‐intent (chemo)radiation who have good WHO PS, patients with combined handgrip weakness and low FFMI have the worst prognosis.